Os efeitos do Programa Bolsa Família sobre a pobreza e a desigualdade: Um balanço dos primeiros quinze anos - Pedro H. G. Ferreira de Souza; Rafael Guerreiro Osorio; Luis Henrique Paiva; Sergei Soares (Instituto de Pesquisa Econômica Aplicada (IPEA), 2019)
– The goal of the study is to evaluate the targeting of the Bolsa Família Programme and its impacts on the reduction of poverty and inequality. To that end, we have used data from the 2001-2015 standard National Household Sample Survey (Pesquisa Nacional por Amostra de Domicílios - PNAD) and from the 2016 and the 2017 longitudinal PNAD. The results support the findings of previous studies. Bolsa Família is by far the most progressive transfer ever enacted by the federal government. Its excellent targeting explains why, despite its small budget (0.5 per cent of GDP) and its limited representation in household income as reflected by PNAD (0.7 per cent), the programme has such a significant impact on poverty reduction: its transfers reduce poverty by 15 per cent and extreme poverty by 25 per cent. Dynamic decompositions of the Gini coefficient suggest that the programme was responsible for the 10 per cent of the reduction in inequality between 2001 and 2015. From 2001 to 2006 (the period during which the programme grew most significantly), Bolsa Família accounted for almost 17 per cent of the observed reduction in inequality. Findings suggest that the targeting of the Programme is already very good and that the main restraining factor of the Programme's impact on poverty is not targeting, but rather the low value of the transfers.
Keywords: D31; D78; I38; 330; poverty; inequality; redistribution; cash transfers